Penerapan Teknik Objektive Camera Angle Dalam Membangkitkan Dramatis Film Pulang - Ahmad Umar Dhany; Dani Manesah (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
The film "Pulang" is a short drama genre film with a family style, This film was made as an entertainment medium that can provide information to audience about a family where Karin's mother has a an illness that made him forget his memory even of his own child, however The child is still trying to take care of and make the mother's memory return to normal. The final result that will be produced is a work of fiction film entitled "Pulang" the process of taking pictures uses the application of objective techniques camera angle by using the audience's point of view so that the audience can feel the same thing experienced by Karin as the main character in this film